Arduino computer vision programming : design and develop real-world computer vision applications with the powerful combination of OpenCV and Arduino /: design and develop real-world computer vision applications with the powerful combination of OpenCV and Arduino. (2015) - Özkaya, Özen; Yıllıkçı, Giray
No abstract available